Enhancing the photocatalytic performance and chemical durability of AZ31 magnesium alloy by incorporating two types of nanoparticles through plasma electrolytic oxidation - Mosab Kaseem; Abdullah H. Alluhayb; Talitha Tara Thanaa; Arash Fattah-alhosseini; Mohammad Alkaseem (Journal of Magnesium and Alloys)
The difficulty in achieving a balance between photocatalytic efficiency and chemical robustness has been a barrier to the broad use of MgO as a versatile material, mainly because of its restricted surface activity. To overcome this, a novel surface modification technique is proposed. It involves the integration of highly stable SnO2 and WO3 nanoparticles, which are known to enhance surface activity. This approach aims to achieve an optimal balance between efficiency and stability by finely tuning the structure-surface reactivity relationship. The technique utilizes a plasma electrolytic oxidation (PEO) method. In this method, both the AZ31 Mg alloy substrate and SnO2/WO3 precursors undergo simultaneous oxidation. This is induced by high-energy plasma generated through high voltage. The results demonstrate that this process yields a MgO layer with a homogeneous dispersion of SnO2 and WO3 nanoparticles, significantly enhancing its overall performance. Corrosion measurements demonstrated enhanced electrochemical stability against chloride ions. The dual incorporation resulted in a hybrid film exhibiting a corrosion current density value of 7.57 × 10−11 A/cm2 and a high outer layer resistance of 5.17 × 107 Ω.cm2. Additionally, the dual incorporation of SnO2 and WO3 nanoparticles enhances the photocatalytic activity of AZ31 Mg towards tetracycline degradation. This results in a photocatalytic efficiency of 89.54% within 2 h of exposure to visible light using the BA-W-Sn sample, which outperforms other samples. This integrated strategy enables the study to contribute significantly to expanding the practical applications of MgO-based materials. It does so by simultaneously enhancing their photocatalytic activity and chemical stability.